Evaluating Sensory Acuity as a Marker of Balance Dysfunction After a Traumatic Brain Injury: A Psychophysical Approach - Pilkar, Rakesh; Karunakaran, Kiran K.; Veerubhotla, Akhila; Ehrenberg, Naphtaly; Ibironke, Oluwaseun; Nolan, Karen J. (Frontiers in Neuroscience, 2020)
There is limited research on sensory acuity i.e. ability to perceive external perturbations via body-sway during standing in individuals with a traumatic brain injury (TBI). It is unclear whether sensory acuity diminishes after a TBI and if it is a contributing factor to balance dysfunction. The objective of this investigation is to first objectively quantify the sensory acuity in terms of perturbation perception threshold (PPT) and determine if it is related to functional outcomes of static and dynamic balance. Ten individuals with chronic TBI and eleven age-matched healthy controls (HC) performed PPT assessments at 0.33, 0.5 and 1 Hz horizontal perturbations to the base of support in the anterior-posterior direction, and a battery of functional assessments of static and dynamic balance and mobility (Berg balance scale (BBS), timed-up and go (TUG) and 5-meter (5MWT) and 10-meter walk test (10MWT)). A psychophysical approach based on Single Interval Adjustment Matrix Protocol (SIAM), i.e., a yes-no task, was used to quantify the multi-sensory thresholds of perceived external perturbations to calculate PPT. A mixed-design analysis of variance (ANOVA) and post-hoc analyses were performed using independent and paired t-tests to evaluate within and between-group differences. Pearson correlation was computed to determine the relationship between the PPT and functional measures. The PPT values were significantly higher for the TBI group (0.33 Hz: 2.97±1.0, 0.5 Hz: 2.39±0.7, 1 Hz: 1.22±0.4) compared to the HC group (0.33 Hz: 1.03±0.6, 0.5 Hz: 0.89±0.4, 1 Hz: 0.42±0.2) for all three perturbation frequencies (p<0.006 post Bonferroni correction). For the TBI group, the PPT for 1 Hz perturbations showed significant correlation with the functional measures of balance (BBS: r = -0.66, p = 0.037; TUG: r = 0.78, p = 0.008; 5MWT: r = 0.67, p = 0.034, 10MWT: r = 0.76, p = 0.012). These findings demonstrate that individuals with TBI have diminished sensory acuity during standing which may be linked to impaired balance function after TBI.